2017
DOI: 10.1177/1060028017723935
|View full text |Cite
|
Sign up to set email alerts
|

Olaratumab: A Novel Platelet-Derived Growth Factor Receptor α-Inhibitor for Advanced Soft Tissue Sarcoma

Abstract: Olaratumab, in combination with doxorubicin, represents a novel treatment strategy for advanced soft tissue sarcoma and provides a significant survival advantage for this rare disease state with limited treatment options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Given the association between PDGF over-activity and malignant tumors, different kinds of PDGF inhibitors have been developed. These inhibitors include the fully human IgG1 monoclonal antibody against PDGFRα named olaratumab ( 108 ), and multi-target TKIs such as cediranib, imatinib, and sorafenib ( Table 1 ).…”
Section: Which Rtk Is the Key Target?mentioning
confidence: 99%
“…Given the association between PDGF over-activity and malignant tumors, different kinds of PDGF inhibitors have been developed. These inhibitors include the fully human IgG1 monoclonal antibody against PDGFRα named olaratumab ( 108 ), and multi-target TKIs such as cediranib, imatinib, and sorafenib ( Table 1 ).…”
Section: Which Rtk Is the Key Target?mentioning
confidence: 99%
“…Different studies quote different survival data based on treatment approach applied and a uniform consensus does not exist regarding survival rates. Important prognostic factors include tumour size and the presence or absence of metastasis at the time of diagnosis 23. In one study, patients with angiosarcoma showed better 5-year survival if the primary lesion was <5 cm.…”
Section: Discussionmentioning
confidence: 99%
“…Controversy exists regarding the value of currently available treatments, such as chemotherapy, to reduce the rate of metastasis [6]. Prognosis for metastatic STS is poor, with overall survival of approximately 18 months [7] and estimated five-year survival of 16% [8].…”
Section: Introductionmentioning
confidence: 99%
“…Management of STS requires a multidisciplinary approach which can include surgery, chemotherapy, and radiation therapy (RT). For patients with low-risk disease and relatively low probability of metastatic spread, local resection (often in conjunction with RT) is largely efficacious as reflected in the high five-year survival rate of 83% [8]. In contrast, patients with high-risk disease generally have poorer survival, despite effective local control.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation